Potential of agricultural by-products as sources of mineral nutrients in ruminant diets - Kabaija, E.; Little, D.A. (International Livestock Centre for Africa, 1989)
Examines crop residues and agro-industrial by-products available in Ethiopia as potential ruminant feeds in relation to their potential to supply essential dietary minerals. Studies composition, digestibility, mineral content, mineral availability of diets and mineral disappearance from ox rumen.